2016
DOI: 10.1038/srep30729
|View full text |Cite
|
Sign up to set email alerts
|

Core-Shell Silver/Polymeric Nanoparticles-Based Combinatorial Therapy against Breast Cancer In-vitro

Abstract: The current study aimed at preparing AgNPs and three different core-shell silver/polymeric NPs composed of Ag core and three different polymeric shells: polyvinyl alcohol (PVA), polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP). Thereafter, the core/shell NPs were loaded with a chemotherapeutic agent doxorubicin (DOX). Finally, the cytotoxic effects of the different core-shell Ag/polymeric NPs-based combinatorial therapeutics were tested in-vitro against breast cancer (MCF-7) and human fibroblast (1BR h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…However, NPs were well-dispersed in the composite (as shown in the TEM micrographs) in spite of their low zeta potential. This is may be attributed to the stabilizing effect of the large molecular weight of PVP to AgNPs through steric stabilization as mentioned by Elbaz et al [48]. The AgNPs produced by reduction via the NaBH 4 are stabilized by the capping effect of PVP.…”
Section: Particle Size Distribution and Zeta Potentialmentioning
confidence: 84%
“…However, NPs were well-dispersed in the composite (as shown in the TEM micrographs) in spite of their low zeta potential. This is may be attributed to the stabilizing effect of the large molecular weight of PVP to AgNPs through steric stabilization as mentioned by Elbaz et al [48]. The AgNPs produced by reduction via the NaBH 4 are stabilized by the capping effect of PVP.…”
Section: Particle Size Distribution and Zeta Potentialmentioning
confidence: 84%
“…It has been reported that cellular uptake of free DOX was mediated by a passive diffusion, while the internalization of DOX-loaded nanoparticles involved an endocytosis mechanism [47]. The endocytosis leading to increase accumulation of drug into cells compared to passive diffusion [48]. The drug loading mode (non-covalent complexation or covalent conjugation) was also reported as a crucial factor which influences therapeutic efficiency, so that the non-covalently loaded DOX to nanoparticles exhibited significantly higher cytotoxicity than covalently conjugated DOX [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that the AgNPs can be used as an effective drug delivery system for targeting cancer because of its pHsensitive properties. AgNPs in BNCs system exhibit the active drug release in the acidic environment of cancer cells which increases bioavailability and therapeutic concentration of drug to cancer cells compared to healthy cells [41,42].…”
Section: The Surface Zeta Potentialmentioning
confidence: 99%